Integrating GIS-based and geophysical techniques for groundwater potential assessment in Halabja Said Sadiq sub-basin, Kurdistan, NE Iraq - Hawber A. Karim; Diary A. Al-Manmi (Tikrit Journal of Pure Science)
Groundwater is an important resource in Halabja Said Sadiq sab-basin, Sulaymaniyah district for agricultural and other uses. Continuous dramatic extraction of groundwater from legal and illegal wells led to a severe decline in the water table for the last thirty years. The objectives of this study are to delineate the groundwater productivity zones by combining the geographic information system and geoelectrical survey, which serves to recognize the locations of good groundwater storage and recharge zones. The Halabja Said Sadiq sub-basin has been selected as a case study to delineate the groundwater productivity zones. Four geoelectrical resistivity profiles conducted with electrode spacing 10 m and the length of the profiles is equal to 710 m.  Themes such as hydrogeology, land use/land cover, topography, drainage density, soil type, slope, lineaments and rainfall maps are created. The thematic maps made with GIS platform and appropriate weights put to the attributes taking into account the influence on the storage potential of groundwater. The results of geoelectrical profiles revealed that the aquifer thickness is 150 m. Three zones of groundwater potential delineated which are low, moderate and high and cover 33 %, 24 %, and 42 % of the total area respectively. Spatially, the highest zone is located along with the Quaternary deposits which characterized by high lineament density, low slop, and pediment deposition